Assessment of various etiological factors of puberty menorrhagia in rural central India - Deepti Gupta; Shradhha Agrawal; Surabhi Gupta (Barpeta Obstetrics and Gynaecological Society, 2021)
Background: Puberty menorrhagia is characterized by bleeding of long duration anywhere between menarche and 19 years. It takes 5-8 years for development of regular menstrual cycle from menarche and during this period the adolescents experience menstrual abnormalities. Objective: The present study was conducted to evaluate the etiologies of puberty menorrhagia in adolescent girls of rural India. Methodology: Retrospective, observational study was carried out over a 2 years period on adolescents presenting with bleeding per vaginum. Permission to use medical records was taken from the medical records. BMI, duration of symptoms, menstrual pattern, ultrasonographic findings, diagnosis, treatment etc. were captured and analysis carried out. Results: The commonest etiology was immaturity of hypothalamic-pituitary ovarian axis, followed by PCOS, endocrine or hematological disorders. Only 25% were treated with hormonal therapy. Reassurance therapy of adolescent and her parents was found to be of utmost importance. Conclusion: The commonest cause of abnormal bleeding in adolescents is hypothalamic-pituitary ovarian axis immaturity which results in anovulation and then followed by PCOS, endocrine and other disorders requiring diagnostic testing.